2016
DOI: 10.1016/j.jsams.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

No association between surface shifts and time-loss overuse injury risk in male professional football

Abstract: Hägglund, M. (2015). No association between surface shifts and timeloss overuse injury risk in male professional football. Journal of Science and Medicine in Sport,19,[218][219][220][221] Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på www.elsevier.com: http://dx.doi.org/10. 1016/j.jsams.2015.06.001 This is the final text version of the article, and it may contain minor differences from the journal's pdf version.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…41 Prior biomechanical studies have shown no difference in physiological responses after soccer matches or recovery after soccer-specific exercises for elite players on AT and NG. 26,29,36,48 In a study specifically examining foot loading patterns, no time or performance differences were seen between the 2 surfaces. 19 Additionally, players' preferences may be influenced by the more difficult physical recovery, or the perception of a more difficult recovery, that they face after competition on AT.…”
Section: Injury Incidencementioning
confidence: 98%
See 1 more Smart Citation
“…41 Prior biomechanical studies have shown no difference in physiological responses after soccer matches or recovery after soccer-specific exercises for elite players on AT and NG. 26,29,36,48 In a study specifically examining foot loading patterns, no time or performance differences were seen between the 2 surfaces. 19 Additionally, players' preferences may be influenced by the more difficult physical recovery, or the perception of a more difficult recovery, that they face after competition on AT.…”
Section: Injury Incidencementioning
confidence: 98%
“…Prior injury surveillance studies during match play in male and female elite athletes, 8,9,12,16,30,31 male and female intercollegiate athletes, 10,20 and male and female youth-level athletes 4,44,46 have not found any significant differences in acute injury rates between NG and AT. 29 AT has been found to have a decreased rate of injury in a cohort of elite male athletes 1 and male and female intercollegiate athletes. 33,34 Ankle sprains have been significantly more numerous on AT, 12,16 whereas quadriceps injuries in men have been less numerous on AT compared with NG.…”
mentioning
confidence: 95%
“…Activity-related lower limb overuse, insidious onset Campanelli, 2015 Excessive strain and load on joints, which may lead to the development of overuse Multi-factorial injuries of the lower limb associated with intensive weight bearing exercise Foch, 2015 Increased muscle strain over the period of many runs Fullem, 2015 Injury due to harder training Galloway, 2013 Pathologic condition that is dominated by an incomplete or maladaptive repair process Goffar, 2013 Overuse injury due to required extended periods of walking and marching under heavy loads. Kerr, 2016 Repetitive nature of the activity -overuse Khan, 2018 Bone stress injuries Koch, 2016 Being a training or match injury when symptoms developed or aggravated usually caused by repeated micro-trauma without a single, identifiable event responsible for the injury Kollock, 2016 Overuse injuries due to large amounts of physical training Kristenson, 2016 Injuries with insidious onset and no known trauma mechanism Malliou, 2014 Chronic mechanism of injury (overuse = gradually onset).…”
Section: First Author Year Of Study Overuse Injury Definition Bonannmentioning
confidence: 99%
“…Case-control study 2 (++) Fullem, 2015 Clinical review 4 Galloway, 2013 Clinical review 4 Goffar, 2013 Cross-section study 3 Kerr, 2016 Descriptive epidemiology study 3 Khan, 2018 Case series 3 Koch, 2016 Prospective cohort 2 (++) Kollock, 2016 Meta-analysis 1 (+) Kristenson, 2016 Follow up-study 3 Malliou, 2014 Cross-section study 3 Pensgaard, 2018 Prospective cohort study 2 (+) Reinking, 2015…”
Section: Sign 50 Gradesmentioning
confidence: 99%
“…However, the development of 'football turf ' AGPs and the need to meet minimum standards set by FIFA and the Football Association has been aimed at reducing the risk of injury (Almutawa et al 2014). Recent studies (Almutawa et al 2014;Andersson, Ekblom, and Krustrup 2008;Bjorneboe, Bahr, and Andersen 2010;Kristenson et al 2016;Soligard, Bahr, and Andersen 2010) have found no increased risk of injury when newer AGPs are compared to natural grass. In addition to examinations of the risk of injury associated with AGPs, recent mainstream press reports in the United Kingdom have also linked the regular use of AGPs that use rubber crumb infill with an increased risk of cancer, because the recycled car tyres that are often used to make rubber crumb infill have been reported to contain potentially harmful carcinogens (Daily Telegraph, February 17, 2016).…”
Section: Introductionmentioning
confidence: 99%